2012
DOI: 10.1080/1533290x.2012.705148
|View full text |Cite
|
Sign up to set email alerts
|

The Knowledge Base as an Extension of Distance Learning Reference Service

Abstract: This study explores knowledge bases as extension of reference services for distance learners. Through a survey and follow-up interviews with distance learning librarians, this paper discusses their interest in creating and maintaining a knowledge base as a resource for reference services to distance learners. It also investigates their perceptions about the feasibility and practicality of a reference knowledge base. Primary findings indicate that the majority of participants view a knowledge base as an extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In a survey of distance learning librarians on their use of a knowledge bases in reference transactions conducted in 2011, 56 percent of the respondents reported that they built the information repositories from local reference transactions. In addition, 50 percent of those who answered the survey said that they developed these knowledge bases as a resource for librarians to have access to the information exchanged in reference transactions (Casey, 2012). So, in effect, the majority of distance learning librarians who participated in the survey were developing a knowledge base for informal learning from virtual transactions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a survey of distance learning librarians on their use of a knowledge bases in reference transactions conducted in 2011, 56 percent of the respondents reported that they built the information repositories from local reference transactions. In addition, 50 percent of those who answered the survey said that they developed these knowledge bases as a resource for librarians to have access to the information exchanged in reference transactions (Casey, 2012). So, in effect, the majority of distance learning librarians who participated in the survey were developing a knowledge base for informal learning from virtual transactions.…”
Section: Literature Reviewmentioning
confidence: 99%